Effects of Work from Home in the COVID-19 Pandemic – Polish Employee’s Perspective - Iwona OLENIUCH (Communications of International Proceedings, 2021)
Before the pandemic, only 2.13% of the Poles worked remotely. COVID-19 made many Polish employees perform work from home (WFH), which was something completely new and unexpected for them. It could be assumed that the lack of previous experience and the sudden introduction of this change would cause a number of difficulties. One could suppose – based on the experience of other economies – that it would also bring some benefits for them. The purpose of the paper was to present the results of a pilot study which identified the difficulties and benefits of remote working reported by Polish employees implementing WFH due to pandemic constraints. The research was carried out in April 2021, i.e. a year after the outbreak of the disease, and the proprietary questionnaire and the survey was used. The data obtained in the research were analyzed with the use of descriptive statistics methods. The analysis allowed building rankings of the benefits and difficulties of WFH and relate them to those experienced by authors from other countries, where remote working has been more common and known for years. The paper is part of the research challenges identified by researchers after the COVID-19 outbreak. The conclusions can be used as a starting point to create motivation and support tools for employees, based on the diagnosis of both their needs and concerns. They can also be applied in comparative studies, both with the opinions of employees from other countries, and with the opinions of employers who implemented WFH as a result of the COVID-19 pandemic.
Keywords: COVID-19; remote work; WFH; work from home; well-being